Metamodel of National Enterprise Architecture - Sobczak, Andrzej (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
In order to effectively carry out digital transformation of the state is necessary to use the correct methodology tools. One of the tools to support the conduct of this transition can be a state enterprise architecture. This article attempts to define this concept and presents the author’s metamodel allowing for uniform application of the concepts used for architectural diagrams. This makes it possible to build a consistent description of the state in terms of architecture.